(untitled) (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2023)
Today it seems normal for a woman to aspire to be a professional and to do so enroll in the university to study the career that most appeals to her, however, this was not always the case since one of the conquests that women have achieved in the last century is to be able to fully access professional education. In this sense, this article takes a tour of the incessant struggle of women to obtain gender equality in the law career.